The rhetoric of paintings; The Balinese Malat and the prospect of a history of Balinese ideas, imaginings, and emotions - Worsley, Peter (Wacana, Journal of the Humanities of Indonesia, 2020)
Balinese paintings from the nineteenth and early twentieth centuries shed light on how painters and their works speak to their viewers both about how Balinese in this period knew, imagined, thought, and felt about the world in which they lived, and about the visual representation and communication of these ideas, imaginings, and feelings through the medium of narrative paintings. In this paper I discuss five Balinese paintings of the Malat. The first two illustrate the episode in which Raden Misa Prabangsa stabs Raden Ino Nusapati’s horse. The third and fourth paintings illustrate Prabu Melayu’s rescue of his sister Princess Rangkesari of Daha from the court of the King of Lasem, and the fifth, the reuniting of Princess Rangkesari with her parents, the King and Queen of Daha. However, before I consider the paintings, I discuss briefly a number of historiographical issues concerning the reception of ideas, imaginings, and feelings conveyed in these five narrative paintings of the Malat and which need to be kept in mind when assessing interpretations of them.